The Relationship between Supervisor Ratio and Organizational Turnover: The Mediating and Moderating Effects of Engineers. Issue 4 (1st October 2016) - Iammartino, Ronald; Bischoff, John E.; Willy, Christopher
Abstract: The main purpose of this study was to examine the association between organizational supervisor ratio and engineer supervisor percentage with engineer turnover and total organizational turnover. Our study has new implications for the effects of supervisor ratio, which has not been specifically investigated in past engineering management research. Hierarchical multiple regression analysis was used on 85 organizational-level datasets from 17 large U.S. federal agencies. The findings suggest that engineer turnover is negatively related to supervisor ratio and positively related to engineer supervisor percentage. Mediation and moderation effects were observed. The study found partial mediating effects of engineer supervisor percentage in weakening the negative association between supervisor ratio and engineer turnover. Engineer turnover was also found to moderate the negative association between supervisor ratio and non-engineer turnover rate. This study further provides a theory-building framework for the role of organizational supervisor ratio in mitigating turnover risk for both engineers and all other knowledge workers in interdisciplinary work environments. Applying value congruence theory, engineering managers can use these findings to understand the role of supervisor ratio in organizational design and its impact on engineer turnover. We conclude with practical engineering management recommendations for engineer-manager training programs, engineer mentorship, organizational strategic communications, and the strategic deployment of engineers across the organization.